Host MKRN1-Mediated Mycobacterial PPE Protein Ubiquitination Suppresses Innate Immune Response - Dou, Yafeng; Xie, Yan; Zhang, Lingyun; Liu, Sheng; Xu, Dandan; Wei, Yuying; Li, Yongshuai; Zhang, Xiao-Lian (Frontiers in Immunology, 2022)
Mycobacterium tuberculosis (Mtb), as an important intracellular pathogen, can invade and survive in macrophages and is capable of escaping the clearance of immune system. Despite decades of research efforts, the precise mechanism of immune escape and the virulence factors encoded by Mtb involved remain to be explored. Mtb-specific genomic regions of deletion (RD)-encoded proteins and PE/PPE family proteins have been implicated in immune evasion. Here, we screened more than forty RD-encoded proteins which might be involved in facilitating bacterial survival in macrophages, and found that a Mtb PPE68/Rv3873 protein, encoded by Mtb-RD1, is essential for efficient Mtb intracellular survival in macrophages. In terms of mechanism, we found that the ubiquitin ligase (E3) Makorin Ring Finger Protein 1 (MKRN1) of macrophage interacted with PPE68 and promoted the attachment of lysine (K)-63-linked ubiquitin chains to the K166 site of PPE68. K63-ubiquitination of PPE68 further bound src homology 2 domain-containing protein tyrosine phosphatase 1 (SHP1) to suppress K63-linked polyubiquitin chains of tumor necrosis factor receptor-associated factor 6 (TRAF6), and then remarkably suppressed TRAF6-driven NF-κB and AP-1 signaling and TNF-α, IL-6 and NO production. We demonstrate that the K63-linked ubiquitination of PPE68 by MKRN1 contributed to the PPE68-mediated mycobacterial immune escape. Our finding identifies a previously unrecognized mechanism by which host MKRN1-mediated-ubiquitination of mycobacterial PPE protein suppresses innate immune responses. Disturbing the interaction between host MKRN1 ubiquitin system and mycobacterial PPE protein might be a potential therapeutic target for tuberculosis.